(untitled) - Legge, J. D. (New York, 1972)
Sukarno was one of the great charismatic leaders of the post-war world. To some he was the architect of his nation, to others a flamboyant and extravagant dictator.
Keywords: Indonesia,Sukarno; History,Biography; 20th century